Using Incredibles 2 Animation Movie in Improving Students’ Writing Descriptive Text - Euis Rahayu Ningsih; Aswir Aswir; Muhamad Sofian Hadi (Universitas Cokroaminoto Palopo, 2021)
This study aims to analyze whether in ten grade TKJ 2 students of SMK Islamiyah Ciputat, Incredibles 2 Animation Movie could improve the writing skill of descriptive text. There were 36 students in this study as a sample. The method used is a quantitative approach with a pre-experimental research design. When collecting data for students, the writer used the pre-test and post-test. The data results show that the pre-test score of total students is 1,862 with a mean score of 51.72. Then, with a mean of 80.67, the post-test score for the total students is 2,904. For the pre-test and post-test results, T-test analysis is used. The data result calculation shows that t was 25.402 at the significance level of 0.05 was 2,030. That also means that the assumption () is accepted and assumes that () is rejected. The writer concluded that using Incredibles 2 Animation Movie in teaching and learning of writing descriptive text is useful for students